Cancer‐associated missense mutations enhance the pluripotency reprogramming activity of OCT4 and SOX17. (17th October 2019) - Srivastava, Yogesh; Tan, Daisylyn Senna; Malik, Vikas; Weng, Mingxi; Javed, Asif; Cojocaru, Vlad; Wu, Guangming; Veerapandian, Veeramohan; Cheung, Lydia W. T.; Jauch, Ralf
Abstract : The functional consequences of cancer‐associated missense mutations are unclear for the majority of proteins. We have previously demonstrated that the activity of SOX and Pit‐Oct‐Unc (POU) family factors during pluripotency reprogramming can be switched and enhanced with rationally placed point mutations. Here, we interrogated cancer mutation databases and identified recurrently mutated positions at critical structural interfaces of the DNA‐binding domains of paralogous SOX and POU family transcription factors. Using the conversion of mouse embryonic fibroblasts to induced pluripotent stem cells as functional readout, we identified several gain‐of‐function mutations that enhance pluripotency reprogramming by SOX2 and OCT4. Wild‐type SOX17 cannot support reprogramming but the recurrent missense mutation SOX17‐V118M is capable of inducing pluripotency. Furthermore, SOX17‐V118M promotes oncogenic transformation, enhances thermostability and elevates cellular protein levels of SOX17. We conclude that the mutational profile of SOX and POU family factors in cancer can guide the design of high‐performance reprogramming factors. Furthermore, we propose cellular reprogramming as a suitable assay to study the functional impact of cancer‐associated mutations. Abstract : Srivastava and Jauch showed that cancer associated mutations accelerate the induction of pluripotency from somatic cells driven by SOX2, OCT4, and SOX17. A recurring mutation in SOX17 increases the stability of the protein and converts this lineage specifier into a pluripotency factor and imparts oncogenicity. Findings emphasize the parallels between pluripotency induction and oncogenic transformation that can be exploited to evaluate somatic variants and to improve cell fate programming.